Enhanced enrichment performance of nickel oxide nanoparticles via fabrication of a nanocomposite with a graphene template1. Issue 30 (3rd April 2015) - Fatima, Batool; Jabeen, Fahmida; Padashbarmchi, Zahra; Najam-ul-Haq, Muhammad
<x xml:space="preserve">Abstract</x> Using graphene as a template after modification with nickel oxide, a nanocomposite with an increased surface area is fabricated and applied to phosphopeptides.